2020
DOI: 10.1002/asia.202000680
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Pb‐Free Perovskite Light Absorbers for Efficient Perovskite Solar Cells with Enhanced Performance

Abstract: Recently, enormous efforts have been made to develop the efficient, lead (Pb) free and stable perovskite solar cells (PSCs). In this regards, various strategies were applied and the optoelectronic properties of various Pb free perovskites such as (CH3NH3)3Sb2I9, (CH3NH3)3Bi2I9, Cs3Sb2I9, Cs3Bi2I9, CH3NH3SnI3 and CH3NH3GeI3 etc have been investigated. However, the photovoltaic performance of the developed PSCs was still low and presence of organic moieties in common hole‐transport materials (HTMs) shows poor st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 43 publications
(50 reference statements)
0
35
0
Order By: Relevance
“…Bismuth (Bi) and antimony (Sb) have the promising features such as air stability and less toxic nature and have the potential to replace the Pb. The perovskite‐like materials with general formula of A 3 B 2 X 9 (A=Cs, CH 3 NH 3 , NH 3 ; B=Bi 3+ or Sb 3+ , X=Cl − , Br − , I − ) can be utilized in photovoltaic applications [30,31] . Previously, some perovskite‐like materials such as (CH 3 NH 3 ) 3 Sb 2 I 9 , Cs 3 Bi 2 I 9 , Cs 3 Sb 2 I 9 , (CH 3 NH 3 ) 3 Bi 2 I 9 and (NH 4 ) 3 Sb 2 I 9 have been introduced as light absorbers for the fabrication of stable Pb free PSCs [30–32] .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bismuth (Bi) and antimony (Sb) have the promising features such as air stability and less toxic nature and have the potential to replace the Pb. The perovskite‐like materials with general formula of A 3 B 2 X 9 (A=Cs, CH 3 NH 3 , NH 3 ; B=Bi 3+ or Sb 3+ , X=Cl − , Br − , I − ) can be utilized in photovoltaic applications [30,31] . Previously, some perovskite‐like materials such as (CH 3 NH 3 ) 3 Sb 2 I 9 , Cs 3 Bi 2 I 9 , Cs 3 Sb 2 I 9 , (CH 3 NH 3 ) 3 Bi 2 I 9 and (NH 4 ) 3 Sb 2 I 9 have been introduced as light absorbers for the fabrication of stable Pb free PSCs [30–32] .…”
Section: Methodsmentioning
confidence: 99%
“…The perovskite-like materials with general formula of A 3 B 2 X 9 (A = Cs, CH 3 NH 3 , NH 3 ; B = Bi 3 + or Sb 3 + , X = Cl À , Br À , I À ) can be utilized in photovoltaic applications. [30,31] Previously, some perovskite-like materials such as (CH 3 NH 3 ) 3 Sb 2 I 9 , Cs 3 Bi 2 I 9 , Cs 3 Sb 2 I 9 , (CH 3 NH 3 ) 3 Bi 2 I 9 and (NH 4 ) 3 Sb 2 I 9 have been introduced as light absorbers for the fabrication of stable Pb free PSCs. [30][31][32] The reported literature showed that the morphological features of the perovskite film influence the photovoltaic performance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, E FB and the conduction band potentials (E CB ) of BiVO 4 and Cu-BiVO 4 are 0.03 eV, À 0.17 eV and 0.01 eV, À 0.19 eV, respectively. The corresponding value of valence band (E VB ) was calculated by the formula: [27]…”
Section: Photocatalytic O 2 Evolution Performance and Mechanism Analysismentioning
confidence: 99%
“…[12][13][14] Therefore, Bi based absorbers have gained a great deal of attention as a lead-free alternative. [15][16][17][18] Johansson et al 17,19 reported Cs 3 Bi 2 I 9 , MA 3 Bi 2 I 9 and CsBi 3 I 10 based solar cells with a PCE of 1.09%, 0.12% and 0.4%, respectively. Singh et al 20 found that the morphology of MA 3 Bi 2 I 9 lms strongly depend on the electron transport layer on the FTO substrate, and c-TiO 2 /meso-TiO 2 ETL based device yielded a PCE of 0.2%.…”
Section: Introductionmentioning
confidence: 99%